2018
DOI: 10.1371/journal.pone.0208598
|View full text |Cite
|
Sign up to set email alerts
|

From pristine aragonite to blocky calcite: Exceptional preservation and diagenesis of cephalopod nacre in porous Cretaceous limestones

Abstract: Aragonite (along with calcite) is one of the most common polymorphs of the crystalline calcium carbonate that forms the skeletal structures of organisms, but it has relatively low preservation potential. Under ambient conditions and in the presence of water, aragonite transforms into calcite, the stable polymorph. Aragonite is also more soluble therefore, in water-permeable siliceous limestones (opokas) that are typical of Upper Cretaceous deposits of Poland and Ukraine, the primary aragonitic skeletons are ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…In our case, the ammonite internal moulds are covered by three layers of material differing from the original shell and hence resulting from a diagenetic transformation. Although likely simplistic, the model proposed here is a transformation of the nacreous aragonitic layer into the equant calcite layer similarly to observation in Janiszewska et al (2018). Due to the low-oxygen conditions and in presence of organic matter from the shell internal chambers and periostracum (i.e., external organic coating layer of the shell; Lowenstam and Weiner, 1989), both external and internal prismatic aragonite layers were transformed into fibrous glauconitic coatings.…”
Section: Taphonomical and Paleoenvironemental Resultssupporting
confidence: 52%
“…In our case, the ammonite internal moulds are covered by three layers of material differing from the original shell and hence resulting from a diagenetic transformation. Although likely simplistic, the model proposed here is a transformation of the nacreous aragonitic layer into the equant calcite layer similarly to observation in Janiszewska et al (2018). Due to the low-oxygen conditions and in presence of organic matter from the shell internal chambers and periostracum (i.e., external organic coating layer of the shell; Lowenstam and Weiner, 1989), both external and internal prismatic aragonite layers were transformed into fibrous glauconitic coatings.…”
Section: Taphonomical and Paleoenvironemental Resultssupporting
confidence: 52%
“…All these methods highlight the excellent preservation of the aragonitic microstructures and original minerals in C. giganteum shells, even showing preservation of original nacre inside the aperture of the shells (Figures 2f and 2h). The presence of preserved nacre is an indication of excellent preservation since this microstructure is even more susceptible to diagenesis than other aragonite microstructures (e.g., cross lamellar aragonite) due to its high organic matter content (Janiszewska et al, 2018). Despite the good preservation, detailed observations revealed that some parts of the shells were affected by boring or represented aragonite that was precipitated later in the animal's life history on the inside of the whorls (see Figures 2b–2d).…”
Section: Methodsmentioning
confidence: 99%
“…Both aragonite as well as calcite crystals are 3-5 μm in size. The preservation of the original shell mineralogy, in particular of meta stable aragonite, appears to depend on several factors; most important are (1) reducing conditions within the host sediment (hall & Kennedy 1967), (2) low permeability of the host sediment (hall & Kennedy 1967;andaliB 1973;janisZeWsKa et al 2018), and (3) seawater composition at the time when the aragonitic fossils became embedded.…”
Section: G Transformation Of the (White) Aragonitic Shell Into (Browmentioning
confidence: 99%